Exploring late Paleolithic and Mesolithic diet in the Eastern Alpine region of Italy through multiple proxies. Issue 2 (11th September 2020) - Oxilia, Gregorio; Bortolini, Eugenio; Badino, Federica; Bernardini, Federico; Gazzoni, Valentina; Lugli, Federico; Romandini, Matteo; Radini, Anita; Terlato, Gabriele; Marciani, Giulia; Silvestrini, Sara; Menghi Sartorio, Jessica C.; et al.
Abstract: Objectives: The analysis of prehistoric human dietary habits is key for understanding the effects of paleoenvironmental changes on the evolution of cultural and social human behaviors. In this study, we compare results from zooarchaeological, stable isotope and dental calculus analyses as well as lower second molar macrowear patterns to gain a broader understanding of the diet of three individuals who lived between the end of the Late Pleistocene and the Early Holocene (ca., 17–8 ky cal BP) in the Eastern Alpine region of Italy. Materials and methods: We analyze individuals buried at the sites of Riparo Tagliente (Verona), Riparo Villabruna, and Mondeval de Sora (Belluno). The three burials provide a unique dataset for diachronically exploring the influence of climatic changes on human subsistence strategies. Results: Isotopic results indicate that all individuals likely relied on both terrestrial and freshwater animal proteins. Even though dental calculus analysis was, in part, hindered by the amount of mineral deposit available on the teeth, tooth macrowear study suggests that the dietary habits of the individuals included plant foods. Moreover, differences in macrowear patterns of lower second molars have been documented between Neanderthals and modern humans in the present sample, due to a prevalence of Buccal wear among the former as opposed to higher values of Lingual wear in modern human teeth. Discussion: Isotopic analyses have emphasized the contribution of animal proteins in the diet of the three foragers from the Eastern Alpine region. The possible intake of carbohydrate‐rich plant foods, suggested by the retrieval of plant remains in dental calculus, is supported by the signal of macrowear analysis. Moreover, the latter method indicates that the distribution of macrowear in lower second molars (M2 s) allows us to discriminate between Neanderthals and modern humans within the present reference sample. Overall, our results show these three prehistoric hunter‐gatherers were well adapted to the environment in which they lived exploiting many natural resources.